2019
DOI: 10.1007/s13353-019-00516-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair in cancer initiation, progression, and therapy—a double-edged sword

Abstract: Genomic and mitochondrial DNA molecules are exposed continuously for a damaging activity of chemical, physical, and internal genotoxicants. When DNA repair machinery is not working efficiently, the generation of DNA lesions and mutations leads to carcinogenic transformation. The high number of mutation going up to 10 5 per cell was recognized as a driving force of oncogenesis. Moreover, a high activity of DNA repair genes was hypothesized as a predisposition to metastasis. DNA repair potential has to be taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 39 publications
2
74
0
Order By: Relevance
“…Indeed, a Cox hazard analysis of PanCan patient data revealed that high levels of DSB repair factors which constitute conserved targets of the FX-miRs, such as APLF, DCLRE1C, XRCC4, BRCA1, RAD51, CHEK1, and TOPBP1, correlate with worse cancer patient survival (Figure 4; Supplementary Table S5). This finding is in line with observations that the deregulation of DNA repair is associated with resistance to radiation therapy and cancer progression [68][69][70][71]. In summary, the positionally conserved Xq27.3-residing miRNA genes and their potential DSB repair pathway targets might play a crucial role for cancer progression and outcomes.…”
Section: Fraxa Is a Conserved Hotspot For Mirna Genes Inhibiting Compsupporting
confidence: 89%
“…Indeed, a Cox hazard analysis of PanCan patient data revealed that high levels of DSB repair factors which constitute conserved targets of the FX-miRs, such as APLF, DCLRE1C, XRCC4, BRCA1, RAD51, CHEK1, and TOPBP1, correlate with worse cancer patient survival (Figure 4; Supplementary Table S5). This finding is in line with observations that the deregulation of DNA repair is associated with resistance to radiation therapy and cancer progression [68][69][70][71]. In summary, the positionally conserved Xq27.3-residing miRNA genes and their potential DSB repair pathway targets might play a crucial role for cancer progression and outcomes.…”
Section: Fraxa Is a Conserved Hotspot For Mirna Genes Inhibiting Compsupporting
confidence: 89%
“…Mismatch repair (MMR) pathway acts on nucleotide defects responsible for double strand mismatches. Double strand breaks are detected and repaired by two overlapping pathways, HR and Non-Homologous End-Joining (NHEJ) [23,24].…”
Section: Brca1 and Brca2 Germline Mutationsmentioning
confidence: 99%
“…A recent study showed that Epac could act synergistically with PDE4, an enzyme associated with the incidence of multiple tumors [71], in promoting rectal carcinoma [65]. Although the exact mechanism was not identified, the researchers found correlations between PDE4, Epac, cyclin E1, and the gap junction protein, connexin-43 (Cx43), in tissues obtained from patients diagnosed with invasive rectal carcinoma [65].…”
Section: Role Of Epac In Cancer Cell Proliferationmentioning
confidence: 99%